Nutritional optimization for female elite football players - topical review - de Sousa, M. V.; Lundsgaard, A. M.; Christensen, P. M.; Christensen, L.; Randers, M. B.; Mohr, M.; Nybo, L.; Kiens, B.; Fritzen, A. M. (Scandinavian Journal of Medicine & Science in Sports, 2022)
Women`s football is an intermittent sport characterized by frequent intense actions throughout the match. The high number of matches with limited recovery time played across a long competitive season underlines the importance of nutritional strategies to meet these large physical demands. In order to maximize sport performance and maintain good health, energy intake must be optimal. However, a considerable proportion of female elite football players does not have sufficient energy intake to match the energy expenditure, resulting in low energy availability that might have detrimental physiologic consequences and impair performance. Carbohydrates appear to be the primary fuel covering the total energy supply during match-play, and female elite football players should aim to consume sufficient carbohydrates to meet the requirements of their training program and to optimize the replenishment of muscle glycogen stores between training bouts and matches. However, several macro- and micronutrients are important for ensuring sufficient energy and nutrients for performance optimization and for overall health status in female elite football players. The inadequacy of macro-and micronutrients in the diet of these athletes may impair performance and training adaptations, and increase the risk of health disorders, compromising the player`s professional career. In this topical review, we present knowledge and relevant nutritional recommendations for elite female football players for the benefit of sports nutritionists, dietitians, sports scientists, healthcare specialists, and applied researchers. We focus on dietary intake and cover the most pertinent topics in sports nutrition for the relevant physical demands in female elite football players as follows: energy intake, macronutrient and micronutrient requirements and optimal composition of the everyday diet, nutritional and hydration strategies to optimize performance and recovery, potential ergogenic effects of authorized relevant supplements, and future research considerations.